2006
DOI: 10.1364/ol.31.000368
|View full text |Cite
|
Sign up to set email alerts
|

Temporally and spectrally resolved sampling imaging with a specially designed streak camera

Abstract: We present a novel sampling imaging technique capable of performing simultaneous two-dimensional measurements of the temporal and spectral characteristics of light-emission processes by use of a specially designed streak camera. A proof-of-principle experiment was performed with a homemade multifocal multiphoton fluorescence microscope. The system was calibrated with a Fabry-Perot etalon and a standard fluorophore solution (rhodamine 6G in ethanol) and was shown to have temporal and spectral resolution of 6.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…Other sensors that use a coherent phase relation between the illumination and the detected light, such as optical coherence tomography (OCT) [Huang et al 1991], coherent LiDAR [Xia and Zhang 2009], light-in-flight holography [Abramson 1978], or white light interferometry [Wyant 2002], achieve femtosecond resolutions; however, they require light to maintain coherence (i.e., wave interference effects) during light transport, and are therefore unsuitable for indirect illumination, in which diffuse reflections remove coherence from the light. Simple streak sensors capture incoherent light at picosecond to nanosecond speeds, but are limited to a line or low resolution (20 × 20) square field of view [Campillo and Shapiro 1987;Itatani et al 2002;Shiraga et al 1995;Gelbart et al 2002;Kodama et al 1999;Qu et al 2006]. They have also been used as line scanning devices for image transmission through highly scattering turbid media, by recording the ballistic photons, which travel a straight path through the scatterer and thus arrive first on the sensor [Hebden 1993].…”
Section: Related Workmentioning
confidence: 99%
“…Other sensors that use a coherent phase relation between the illumination and the detected light, such as optical coherence tomography (OCT) [Huang et al 1991], coherent LiDAR [Xia and Zhang 2009], light-in-flight holography [Abramson 1978], or white light interferometry [Wyant 2002], achieve femtosecond resolutions; however, they require light to maintain coherence (i.e., wave interference effects) during light transport, and are therefore unsuitable for indirect illumination, in which diffuse reflections remove coherence from the light. Simple streak sensors capture incoherent light at picosecond to nanosecond speeds, but are limited to a line or low resolution (20 × 20) square field of view [Campillo and Shapiro 1987;Itatani et al 2002;Shiraga et al 1995;Gelbart et al 2002;Kodama et al 1999;Qu et al 2006]. They have also been used as line scanning devices for image transmission through highly scattering turbid media, by recording the ballistic photons, which travel a straight path through the scatterer and thus arrive first on the sensor [Hebden 1993].…”
Section: Related Workmentioning
confidence: 99%
“…Each beamlet is required to scan only a sub-region, and the entire¯eld of view (FOV) is scanned in parallel by the multifocal array so that the imaging speed is approximately equal to the original single-beam rate multiplied by the number of beamlets. Several practical MMM techniques involving microlens array, 16 cascaded splitter, 17 di®ractive optical element (DOE), 12 spatial light modulator (SLM) 18,19 and the Nipkow disk 11 have been widely reported. To further improve imaging speed, Chris Xu's group proposed and developed the temporal focusing multiphoton microscope (TF-MPM) in 2005.…”
Section: Introductionmentioning
confidence: 99%
“…24 Shao et al reported addressable multiregional and multifocal multiphoton microscopy using multifocal excitation pattern matching of samples of interest. 16 However, using this microscope, the scanned area does not accurately match the sample of interest because each focal point scans the same distance. Glück-stad's group reported shape illumination microscopy by combining the raster generalized phase contrast (GPC) technique with a grating.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Multifocal multiphoton microscopy (MMM) which was developed in the late 20th century, can improve the utilization ratio of excitation light energy and achieve video-rate imaging speed at high spatial resolution through the use of microlens array, [3][4][5][6] cascaded beam splitters parallel processing ability of optical system to excite the sample and detect°uorescence emission from multiple foci at the same time. MMM also has almost all the advantages of multiphoton microscopy, such as inherent optical sectioning and less photobleaching and photodamage to the out-offocus sample.…”
Section: Introductionmentioning
confidence: 99%